PERAN PERUSAHAAN MULTINASIONAL DALAM MEMENGARUHI AMANDEMEN UNDANG-UNDANG IMIGRASI TENAGA KERJA ASING DALAM MERESPONS PERMASALAHAN AGING POPULATION DI JEPANG - Bustami, Sirwan Yazid; Zulkarnain, Zulkarnain; Khotimah, Annisa Husnul (Department of International Relations Universitas Satya Negara Indonesia, 2024)
This research aims to analyze role of Japanese multinational corporations in influencing amendments to Foreign Labor Immigration Act in response to shrinking workforce due to aging population in Japan. The role of Japanese multinational corporations is analyzed using a qualitative approach with an analytical descriptive method. Data collection related to role of Japanese multinational corporations was obtained through literature studies and analyzed through several stages, namely data reduction, data presentation, and conclusion drawing. Data reduction was carried out by reviewing data collected to be selected in accordance with analysis of role of Japanese multinational corporations. Furthermore, data analysis was carried out in form of narratives. Finally, conclusion drawing is conducted based on elaboration of concept of interest group and concept of typology of multinational corporations’ power to analyze role of Japanese multinational corporations. Based on results of research, role of Japanese multinational corporations in influencing amendments to Foreign Labor Immigration Act is carried out through use of their power capacities, namely instrumental power, structural power, and discursive power. Instrumental power is exercised through Keidanren’s influence by means of political lobbying, advocacy, consultation, and use of membership networks to create collective pressure on Japanese government. Meanwhile, structural power is exercised through centrality of multinational corporations in Japan’s economic development, resulting in government’s dependence on their investments and innovations and thus changing foreign labor immigration policies. Finally, discursive power is exercised through Keidanren’s influence in constructing discourse of foreign labor immigration as a solution to shrinking workforce due to aging population.